(3GdEfLjds
(3ChdgG (B:s
(3fHOC HYhf Gddg fcJH CQHY UMGFa GdEfLjd GdebOS hChd Pdc HTGQI GdbOjS eJi GdHTjQ s
(3BNQgG (B:s
(3hCLO Ydi MSH Xfi Cfg hdG GdYGde HYjfg cGf jSY GdeUGMa GdecJhHI MbkG JeJ HTGQI GdbOjS jhMfG s
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3cJHJ TgQ CjGQ GdJGQjN GdQGHY SfI Cda hKdKeGFI hSHYI hSHYjf ddCScfOQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdOjGfGJ GdCNQis